Expression of Th1-mediated immunity in mouse lungs induces a Mycobacterium tuberculosis transcription pattern characteristic of nonreplicating persistence - Shi, Lanbo (The National Academy of Sciences, 2003)
The lung is the primary target of infection with Mycobacterium tuberculosis. It is well established that, in mouse lung, expression of adaptive, Th1-mediated host immunity inhibits further multiplication of M. tuberculosis. Here, real-time RT-PCR was used to define the pattern of expression against time of lung infection of key genes involved in Th1-mediated immunity and of selected genes of M. tuberculosis. Inhibition of bacterial multiplication was preceded by increased mRNA synthesis for IFN-γ and inducible NO synthase (NOS2) and by NOS2 protein synthesis in infected macrophages. Concurrently, the pattern of transcription of bacterial genes underwent dramatic changes. mRNA synthesis increased for α-crystallin (acr), rv2626c, and rv2623 and decreased for superoxide dismutase C (sodC), sodA, and fibronectin-binding protein B (fbpB). This pattern of M. tuberculosis transcription is characteristic of the nonreplicating persistence [Wayne, L. G. & Sohaskey, C. D. (2001) Annu. Rev. Microbiol. 55, 139–163] associated with adaptation of tubercle bacilli to hypoxia in vitro. Based on this similarity, we infer that host immunity induces bacterial growth arrest. In IFN-γ gene-deleted mice, bacterial growth was not controlled; NOS2 protein was not detected in macrophages; sodC, sodA, and fbpB transcription showed no decrease; and acr, rv2626c, and rv2623 transcription increased only at the terminal stages of lung pathology. These findings define the transcription signature of M. tuberculosis as it transitions from growth to persistence in the mouse lung. The bacterial transcription changes measured at onset of Th1-mediated immunity are likely induced, directly or indirectly, by nitric oxide generated by infected macrophages.